Positive Influence of Green Supply Chain Operations on Thai Electronic Firms' Financial Performance - K. Y. Tippayawong (2018)
© 2015 The Authors. Published by Elsevier Ltd. Greening the supply chain is about integrating environmental thinking into the chains and their management activities that include reduction, recycling, reuse, and the substitution of materials. With increased public awareness and strict regulations on environmental and sustainability policy, green supply chain management (GSCM) is becoming increasingly important for many Thai firms, especially those in electronics industry. In this work, correlation between GSCM practices and financial performance of Thai electronics firms was investigated, based on evaluation of the firms' current operational performance. A survey questionnaire was used as a self-assessment tool designed within the context of Thai electronics industry considering five main areas of supply chain activities (i) procurement, (ii) manufacturing, (iii) transportation and distribution, (iv) reverse logistics, and (v) greening process, based on integration of SCOR Model, SCM Logistics Scorecard, and GSCM concepts. About 50 respondents were collected as part of analysis. Factor analysis was subsequently conducted to identify main influencing factors from the total of 32 assessment items. From extraction based on GSCM concept, the main factors were 1) green manufacturing practice, 2(green logistics practice, and 3(green sourcing. Multiple regression analysis was performed to derive correlation between the extracted factors of GSCM practice and the firms' financial performance. It was found that both the green manufacturing practice and the green logistics practice were strongly correlated with financial performance, but the green sourcing was not. Cost and complexity appeared to be the major obstacle to implementation of a successful GSCM. More cost effective and easier-to-implement solutions are still needed for future economic and environmental sustainability of the industry.